GAMBARAN TINGKAT KEPUASAN SISWA TENTANG MUTU HIDANGAN PADA PENYELENGGARAAN MAKANAN DAN STATUS GIZI SISWA DI PONDOK PESANTREN ISLAMIYAH PADANG GARUGUR KECAMATAN PADANG BOLAK KABUPATEN PADANG LAWAS UTARA - Sri Wahyuni; Ernawati Nasution; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
The nutritional problems in Indonesia are still a serious problem. It basically starts with an unbalanced intake of nutrients. To meet the intake of balanced nutrients seen from the quality and quantity, as well as the suitability of the amount of a food consumed. The purpose of this study was to determine the description of student satisfaction level on the quality of the dish on the implementation of food and nutritional status of students in Pondok Pesantren Islamiyah Padang Garugur District Padang Bolak Padang Lawas Utara. This research was descriptive research conducted in Pondok Pesantren Islamiyah of Padang Garugur District of Padang Bolak Regency of Padang Lawas Utara with Cross Sectional approach on 76 students, using proportional Stratified Random Sampling technique, data analysis by using frequency distribution and cross tabulation. Data collection by direct interview using questionnaires and weighing Weight using manual scales and measuring height using microtoise. Level of satisfaction with the quality of dishes (portion, color, texture, and taste) of food. Satisfied with the rice portion of 92.1%, not satisfied with the portion of animal side dishes, vegetable side dishes, and vegetables respectively 59.2%, 60.5%, and 55.3%. Not satisfied with the color of animal side dishes, vegetable side dishes, and vegetables respectively as much as 32.9, 42.1, and 14.4%. Not satisfied with the texture of rice, animal side dishes, vegetable side dishes, vegetables respectively 14.5%, 19.7%, 26.3%, and 19.7%. Not satisfied with the taste of animal side dishes, vegetable side dishes, and vegetables respectively as much as 15.8%, 34.2%, and 25.0%. Suggestions in this study to the school is expected to improve the quality of food in Pondok Pesantren Islamiyah Padang Garugur Padang Bolak District Padang Lawas Utara in particular portion and variety of food presented to students so that the nutritional intake of students is met so that the nutritional status of students in the normal category. Keywords: Nutrition Status, Satisfaction Level, Quality of Dishe